The Emergence of Forgiveness in Young Children. Issue 6 (1st April 2018) - Oostenbroek, Janine; Vaish, Amrisha
Abstract : Humans depend greatly on our cooperative relationships. Thus, when our relationships are damaged by transgressions, they need to be repaired. Such repair requires that the transgressor show remorse and the victim forgive. Previous research demonstrates that as transgressors, young children show remorse and attempt to repair the harm they caused. However, it remains unclear when children, as victims, forgive remorseful transgressors. In Study 1, 5‐, but not 4‐year‐olds, ( n = 20 each) were more forgiving of a remorseful transgressor (who did not explicitly apologize) than an unremorseful transgressor. In Study 2, 4‐year‐olds ( n = 20) were more forgiving of an apologetic than unapologetic transgressor. Thus, from early in ontogeny, humans are motivated to repair damaged relationships and thus uphold cooperation.